Incidence of Fodder Cutter (Toka) Hand Injury and their Management in D.I. Khan, Pakistan - Najeebullah; Muhammad shafiq; Syed Wasif Ali Naqvi; Muhammad Hamyun; Muhammad Ali; Shahjahan (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: This study aimed to determine the incidence of toka hand injuries by age, gender, and occupation and their management in D.I. Khan. METHODOLOGY: This descriptive study was conducted from January to December 2023 in the Department of Orthopaedics, DHQ Teaching Hospital, D.I. Khan, Pakistan. Sixty-six patients presenting to the hospital during 2023 with toka hand injuries were selected. Demographic variables were age, gender, and occupation. Research variables were the site of injury and mode of management. All data was analyzed using SPSS version 29. RESULTS: Out of 66 patients, Toka injuries were predominant in females 39(59.09%). Most patients, 51(77.27%), were aged below 30 years, and 42(63.64%) were non-professional by occupation. The most common site of injury was distal to the wrist 33(50%), while it was 27(40.91%) at the wrist level, and 6 (9.09%) were proximal to the wrist. Debridement and stump formation was done in 40(60.60%) while 26(39.40%) patients underwent fixation and stabilization. CONCLUSION: Toka machine injuries mainly result in hand amputations. Safety features must be identified in this region, workers must be adequately educated, and work-related ergonomics must be ensured. Further advancements in management are also needed.